ANALYSIS OF THE ROLE OF BASEFLOW TO FLOOD DISCHARGE IN THE BANDUNG BASIN - Muhammad Fikri S.H., Andi
Flood is a natural disaster that happens in almost all parts of the world. Flood cases occur because of the increasing river discharge and filling out the river capacity. The river flow is composed of two types of flow, namely baseflow and overland flow. At the flood moment, baseflow is one of the most affected components that bring over the size and value of flood discharge. As an area that has a fairly high level of aquifer productivity, surely baseflow has a significant role on flood discharge in Bandung Basin. For this reason, this research was conducted to determine the baseflow contribution on some of Citarum subwatershed when a flood occurs. This research used the Recursive Digital Filter method to separate the flow river into baseflow and overland flow. Discharge data was used from 2018 - 2022. Then, the results were used to calculate the baseflow contribution for every flood event in Bandung basin area. Based on the analysis, it was found that the baseflow contribution of each subwatershed varies each year. The subwatershed that have the largest and smallest baseflow contribution respectively are the Citarik Cikeruh and Cisangkuy subwatershed. Then, based on the geological review, the Citarik Cikeruh subwatershed is more dominated by high level of productivity formations compared to other subwatershed, it makes the Citarik Cikeruh subwatershed is the largest of baseflow contribution, and followed by Cikapundung and Cisangkuy subwatershed. Then from the flood events analysis, it was found that the greater baseflow contribution percentage, the greater duration and peak discharge at the flood event.